1997
DOI: 10.1243/0954405971516400
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effects of autobrazer parameter variations on the quality of return bend joints

Abstract: A temperature monitor that can record brazing temperatures inside an autobrazer for process control and qualification was developed. The monitor was made of a heat exchanger coil instrumented with multiple thermocouples at statistically selected return bend joints that had a high or low probability of leaking. The brazing temperatures recorded at the selected return bends were compared with control temperature profiles for high-quality brazed joints. The results clearly accentuated the disparities in the heati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They observed an abnormal wave pattern on the cutting surface when using the brazed tool due to woven structure of the workpiece. Agba et al 24 investigated the effects of autobrazer parameter variations on the quality of return bend joints. They concluded that the repeatability of the brazing process and the production of high-quality joints can be guaranteed.…”
Section: Introductionmentioning
confidence: 99%
“…They observed an abnormal wave pattern on the cutting surface when using the brazed tool due to woven structure of the workpiece. Agba et al 24 investigated the effects of autobrazer parameter variations on the quality of return bend joints. They concluded that the repeatability of the brazing process and the production of high-quality joints can be guaranteed.…”
Section: Introductionmentioning
confidence: 99%